Optimization for Electric Power Load Forecast - I. A. Ethmane; M. Maaroufi; A. K. Mahmoud; A. Yahfdhou (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Load flow studies are one of the most important aspects of power system planning and operation. The main information obtained from this study comprises the magnitudes and phase angles of load bus voltages, reactive powers at generators buses, real and reactive power flow on transmission lines, other variables being known. To solve the problem of load flow, we use the iterative method, of Newton-Raphson. Analysis of the found results using numerical method programmed on the Matlab software and PSS/E Simulator lead us to seek means of controlling the reactive powers and the bus voltages of the Nouakchott power grid in 2030 year. In our case, we projected the demand forecast at 2015 to 2030 years. To solve the growing demand we injected the power plants in the system firstly and secondly when the production and energy demand are difficult to match due to lack of energy infrastructures in 2030.It is proposed to install a FACTS (Flexible Alternative Current Transmission Systems) system at these buses to compensate or provide reactive power in order to maintain a better voltage profile and transmit more power to customers.